2020
DOI: 10.3389/fpsyg.2020.01564
|View full text |Cite
|
Sign up to set email alerts
|

The Susceptibles, Chancers, Pragmatists, and Fair Players: An Examination of the Sport Drug Control Model for Adolescent Athletes, Cluster Effects, and Norm Values Among Adolescent Athletes

Abstract: Although there are few high-profile cases of adolescent athletes being caught doping, up to a third of young athletes may dope. In order to generate a more accurate understanding of why adolescent athletes dope, it is important to validate models that help to explain this behavior. The aims of this study were 3-fold: firstly, to test the Sport Drug Control Model for Adolescent Athletes (SDCM-AA); secondly, to generate athlete profiles that would help quantify the proportion of athletes who are at risk of dopin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 61 publications
(123 reference statements)
1
11
0
Order By: Relevance
“…In ASDI doping attitude is assessed by four items,) which map on the PEAS items: item #1 about regulation ("Legalizing PEDs would benefit my sport"; "Making PEDs legal would improve sport") and item #2 capturing the perceived need ("In order to be successful in my sport, I need to take PEDs"; "You have to take PEDs to play at the highest level in sport"). Norms are recommended for the composite score, and thus doping attitude is not assessed as a separate construct (Nicholls et al, 2020).…”
Section: Psychometric Scales For Doping Attitudementioning
confidence: 99%
“…In ASDI doping attitude is assessed by four items,) which map on the PEAS items: item #1 about regulation ("Legalizing PEDs would benefit my sport"; "Making PEDs legal would improve sport") and item #2 capturing the perceived need ("In order to be successful in my sport, I need to take PEDs"; "You have to take PEDs to play at the highest level in sport"). Norms are recommended for the composite score, and thus doping attitude is not assessed as a separate construct (Nicholls et al, 2020).…”
Section: Psychometric Scales For Doping Attitudementioning
confidence: 99%
“…Jalleh et al ( 2013 ) reported that morality, reference group opinion and legitimacy are significantly associated with doping attitudes. Nicholls et al ( 2020 ) developed an adaptation of the SDCM aimed at adolescent athletes and found that morality construct was the strongest predictor of attitudes toward doping in this population. The SDCM is likely to be the model that most explicitly represents the theoretical paradigm of the psychological study of the use of doping in sport (Kirby et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Future research using the ADVICE mobile application could assess the impact of the intervention on constructs such as coaching behaviour, the psycho-social variables associated with doping behaviour (eg, doping attitudes, susceptibility and willingness to cheat), 43 among athletes, and doping prevalence among young athletes, to assess the full impact of this tool.…”
Section: Limitations and Future Researchmentioning
confidence: 99%